Vida e conhecimento da vida em Henri Bergson - Rates, Bruno Batista (Universidade Federal de São Carlos, 2012)
The notion of life occupies a special place in Bergson s philosophy. However, far from being univocal, the meaning of this term shows different significations throughout his thought. A decisive change of this concept can be identified in the passage that leads us from the Time and free will to Matter and memory. More specifically, it seems that Bergson offers a new philosophical program in the last chapter of the book of 1896 which is radicalized in 1907 in a way even more surprising. If in a first moment, with the intend to separate space from duration, the French thinker reserves to the biological and empirical dimension of life a character almost completely spacializing and pragmatic , in Creative evolution this dimension will be identified, in a certain sense, to the idea of duration itself, chiefly because of the arrival of a controversial concept, the vital impulse (élan vital). But what takes Bergson to this inflection? We understand that the beginning of this turn and the reasons that take him to produce that change are resulting from two exigencies, related with each other: the first one, directly related to the evidence of the evolutionary theory (Lamarck, Darwin and Spencer) and the necessity of thinking it with the hypothesis of the duration; the second one, tied more specifically to Bergson s thought itself, is concerned to the cohesion that gives to his philosophy a unity of meaning. In other terms: in extending the hypothesis of duration to the material reality in Matter and memory, wouldn t Bergson be forced to amplify his understanding of the organic and the inorganic and, therefore, of life itself? But how can we attribute, at the same time, specificity to the living being, since it now coincides with matter? Can we identify in this point the creative aspect of evolution, the vital impulse (élan vital)? How is it possible to think, within those questions, the indiscernibility between theory of knowledge and theory of life , as it is proposed in Creative evolution? It is in relation to these problems that we try to circumscribe our research.
Keywords: Filosofia; Epistemologia; Metafísica; Vida; Matéria; Bergson; Life; Matter; Epistemology; Metaphysics; CIENCIAS HUMANAS::FILOSOFIA